Macroprudential regulation : review on macroprudential policy and its effectiveness in mitigating systemic risk - Palojärvi, Santeri (My University, 2019)
Macroprudential regulation is still a very young policy field. Aim of macroprudential policy is to mitigate systemic risk and to ensure the stability of financial sector as a whole. After the last financial crisis macroprudential regulation emerged as a way to ensure that future financial crises could be either averted or have its effects softened. Wide variety of different macroprudential instruments that affect different financial sectors offers a capable but a challenging toolbox to be used in countering systemic risk. Macroprudential policy is done on a national basis while the problems are usually larger and affect multiple nations instead of just one nation. The interconnected nature of the financial markets deepens the problems. Wide variety of macroprudential instruments also introduces the risk of macroprudential authority doing damaging macroprudential policy. Main question is that can the macroprudential instruments lower systemic risk? Thesis evaluates the purpose and justification of macroprudential policy, macroprudential instruments, systemic risk from multiple viewpoints, and macroprudential governance issues. It also assesses what type of macroprudential policy is done in European Union and what role ESRB (European Systemic Risk Board) has in macroprudential policy-making and brings several viewpoints to the problems and challenges of macroprudential policy-making. Thesis shows that macroprudential policy has its place among monetary and microprudential policy and at least in theory the instruments can lower systemic risk via smoothening financial cycles. While macroprudential authorities’ capabilities evolve due to more granular data sets and more advanced analysis, some fundamental questions still remain open. These fundamental questions are what systemic risk is and how to quantify it. There are several frameworks that addresses the quantifying of systemic risk but academia should reach a consensus which measuring method would be ideal. Questions arising from financial stability measures are also left open.
Keywords: economic policy, financial stability, macroprudential, regulation, systemic risk